Neuroinflammation as a Common Feature of Neurodegenerative Disorders - Guzman-Martinez, Leonardo; Maccioni, Ricardo B.; Andrade, Víctor; Navarrete, Leonardo Patricio; Pastor, María Gabriela; Ramos-Escobar, Nicolas (Frontiers in Pharmacology, 2019)
Neurodegenerative diseases share the fact that they derive from altered proteins that undergo an unfolding process followed by formation of -structures, and a pathological tendency to self-aggregate in neuronal cells. This is a characteristic of tau protein in Alzheimer´s disease and several tauopathies associated to tau unfolding, synuclein in Parkinson disease and huntingtin in Huntington disease. Usually the self-aggregation products are toxic to these cells, and toxicity spreads all over different brain areas. We have postulated that these protein unfolding events are the molecular alterations that trigger several neurodegenerative disorders. Most interestingly, these events occur as a result of neuroinflammatory cascades involving alterations in the cross-talks between glial cells and neurons as a consequence of the activation of microglia and astrocytes. The model we have hypothesized for Alzheimer´s disease, involve damage signals that promote glial activation, followed by NFβ activation, synthesis and release of proinflammatory cytokines such as TNF-, IL1, IL-6, IL-12 that affects neuronal receptors with an overactivation of protein kinases. These patterns of pathological events can be applied to several neurodegenerative disorders. In this context, the involvement of innate immunity seems to be a major paradigm in the pathogenesis of these diseases. This is an important element for the search for potential therapeutic approaches for all these brain disorders.